The optimisation of Daimlerchrysler's SAP-MRP system through systems analysis, design, and simulation - Kirby, Hugh Christopher (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc)--University of Stellenbosch, 2004.